A Study on Financial Performance of Small Finance Banks with Customer’s Perspective and Satisfaction in Coimbatore - Nazar M. H, Nazar M. H (MANDALIKA : Journal of Social Science, 2025)
Bank is type of financial institution which provides services such as accepting deposit and providing credit facilities to their customers. Reserve Bank of India (RBI) is the governing body that has been taking care of the banking industry in our country. Over the past few years our banking industry has gone through numerous changes on such change has been in initiation Small Finance Banks. Small Finance Bank is those banks which perform basic services such as accepting deposit and lending loans to its customers. The main objective of Small Finance bank is to provide financial inclusion to disadvantaged section that are not served by other banks. This study tries to measure the awareness and perspective of customers towards selected Small Finance Bank in Coimbatore